OS4.2 The long-term disease burden of meningioma patients: results on health-related quality of life, cognitive function, anxiety and depression. (19th September 2018) - Zamanipoor Najafabadi, A H; van der Meer, P B; Boele, F W; Reijneveld, J C; Taphoorn, M J B; Klein, M; van Furth, W R; Dirven, L; Peerdeman, S M; ,
Abstract: Background: Recent systematic reviews reported that meningioma patients have an impaired health-related quality of life (HRQoL) and cognitive function up to 5 years after intervention. We aimed to assess the long-term disease burden of meningioma patients. Material and Methods: In this multicentre cross-sectional study, intracranial meningioma patients at least 5 years (median: 9.9 years) after anti-tumour therapy were included. HRQoL was measured with the generic SF-36 (8 scales and 2 component scores) and the disease-specific EORTC QLQ-BN20 (11 scales/items), and anxiety and depression with the Hospital Anxiety and Depression Scale (HADS: ≤11/21 points is indicative for probable anxiety or depression). Six domains of cognitive function were assessed with a standardised neuropsychological test battery (z-score<-1.5 is defined as a clinically relevant deficit). Generalised linear models were used to compare meningioma patients with healthy controls, corrected for age, sex, educational level and comorbidities. One-sample t-tests were used to compare meningioma patients with normative data of newly diagnosed glioblastoma patients. Patient recruitment and data collection is still in progress. Results: 164 meningioma patients were included (mean age 63.9 years, WHO grade I: 91.7%, surgery: 89.2%, radiotherapy: 14.6%). Compared with 110 controls, meningioma patients had worse HRQoL scores on 4/10 SF-36 scales/component scores: role limitations due to physical problems (mean difference: 11.7, p=0.03) and emotional problems (difference: 13.8, p=0.009), social functioning (difference: 9.5, p=0.016), and the mental component score (difference: 4.4, p=0.011). Meningioma patients scored similar to glioblastoma on 5/11 EORTC QLQ-BN20 scales/items: visual deficits (difference: 1.6, p=0.272), headache (difference: 2.9, p=0.324), seizure (difference: 1.6, p=0.103), drowsiness (difference: 3.7, 0.619), and hair loss (difference: 3.4, p=0.164), but better on other scales/items. Patients suffered from probable anxiety in 14.3% of cases (controls: 3.7%, p=0.015) and depression in 7.5% of cases (controls: 1.9%, p=0.011). Clinically relevant cognitive deficits were found in executive function (10.9%), verbal memory (19.4%), working memory (13.4%), attention (10.3%), information processing (25.0%) and psychomotor speed (14.4%). Conclusion: Almost 10 years after the last anti-tumour treatment, meningioma disease burden is still significant and in some areas comparable to newly diagnosed glioblastoma. A considerable number of patients have impaired HRQoL, suffer from cognitive deficits and report high levels of anxiety and depression.